Strategi Positioning “Gemoy” Prabowo Subianto melalui Media Digital - Sihabudin, M. Maulana Rizik; Helwa Nur Alfa Laila; Kharisma Kharis; Rismayanti; Riska Siti Fatimah (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2023)
This research aims to analyze the transformation of Prabowo Subianto's image from a stern and authoritative figure to a more relaxed and attractive one, focusing on the development of a